COMPARISON OF EFFICIENCY AND MODELLING OF ISLAMIC BANKS AND CONVENTIONAL BANKS IN INDONESIA - Ar Royyan Ramly (Global Review of Islamic Economics and Business, 2016)
This study aims to analyze the efficiency comparison between Islamic banks and conventional banks in Indonesia in 2012-2014. The data in this study were chosen through purposive sampling from 20 Islamic banks and conventional banks in Indonesia. The method used in this study is non-parametric approach with data envelopment analysis (DEA) whereas input and output variables are treated in intermediary function. The input variables are total asset, total saving (third party fund), and price of labor while the output variables are total financing (loans) and total operational expenses. To measure the efficiency level of Islamic banks and conventional banks the independent sample t test is used.The result of the study shows that there is no significant difference of efficiency between Islamic banking and conventional banking in 2014 because of the significant value (2-tailed) only at 0.537 where P-value is higher than α=0.05 Ha is refused. There is no difference of efficiency between Islamic banks and conventional banks in efficiency scale (ES). The empirical factors that affect Islamic banks and Conventional banks efficiency are ROA, CAR, and FDR variables. On the other hand, NPF results insignificantly and affects negatively towards Islamic banks efficiency. Lastly, ROA, NPL, LDR, and CAR had significantly affected Conventional banks efficiency in Indonesia from 2012 to 2014.